Photonic integration for UV to IR applications - Blumenthal, Daniel J. (APL photonics, 2020)
Photonic integration opens the potential to reduce size, power, and cost of applications normally relegated to table- and rack-sized systems. Today, a wide range of precision, high-end, ultra-sensitive, communication and computation, and measurement and scientific applications, including atomic clocks, quantum communications, processing, and high resolution spectroscopy, are ready to make the leap from the lab to the chip. However, many of these applications operate at wavelengths not accessible to the silicon on insulator-based silicon photonics integration platform due to absorption, power handling, unwanted nonlinearities, and other factors. Next generation photonic integration will require ultra-wideband photonic circuit platforms that scale from the ultraviolet to the infrared and that offer a rich set of linear and nonlinear circuit functions as well as low loss and high power handling capabilities. This article provides an assessment of the field in ultra-wideband photonic waveguides to bring power efficient, ultra-high performance systems to the chip-scale and enable compact transformative precision measurement, signal processing, computation, and communication techniques.